Analisis Kematian Larva Nyamuk Aedes agypti Akibat Pemberian Perasan Buah Nanas (Ananas comosus) - Tominik, Victoria Ire; Haiti, Margareta (Jurnal Kesehatan, 2018)
South Sumatra including 11 provinces experienced outbreaks. Aedes agypti is the main vector of dengue fever. Eradication by breaking the life cycle of Aedes agypti (larvae) mosquitoes which are not a health risk and environmentally friendly. Pineapple grows a lot in Indonesia, especially South Sumatra. Bromelin is an enzyme in pineapple which hydrolyzes peptide bonds in the protein content to amino acids. Parts of pineapple meat are used more while the skin and humps are wasted. Objective: to determine the effect of variations in concentration (100%, 75%, 50%, 25%) of pineapple juice (skin, meat, hump/stem) and the time of the death of Aedes agypti mosquito larvae. Research method: pure experimental, June-July 2018. The research subjects were 3000 Aedes agypti instar III larvae, population 2404 larvae, 2100 larvae samples, simple sampling random. Analysis of Pearson test data, One Way Anava test, post hoc LSD and post hoc Duncan, 95% confidence level. There was a relationship between the variation of pineapple juice concentration and larvae mortality with a sig (2-tailed) value of 0.001, insignificant meat and skin but skin and hump/stem or meat and hump/stem are significantly different from the number of mosquito larvae deaths in the first 12 hours of meat 97,67%, skin 96,83%, humps 87,17%. The higher the concentration of the more deaths of Aedes agypti mosquito larvae with the skin part has the same ability as meat and better than hump.